Experiences and Opinions Related to End-of-Life Discussion: From Oncologists' and Resident Physicians' Perspectives - Koh, Su-Jin; Kim, Shinmi; Kim, JinShil; Keam, Bhumsuk; Heo, Dae Seog; Lee, Kyung Hee; Kim, Bong-Seog; Kim, Jee Hyun; Chang, Hye Jung; Baek, Sun Kyung (Cancer research and treatment, 2018)
The aims of this study were to explore how oncologists and resident physicians practice end-of-life (EOL) discussions and to solicit their opinions on EOL discussions as a means to improve the quality of EOL care. A survey questionnaire was developed to explore the experiences and opinions about EOL discussions among oncologists and residents. Descriptive statistics, the t test, and the chisquare test were performed for the analyses. A total of 147 oncologists and 229 residents participated in this study. The study respondents reported diverse definitions of "terminal state," and mostrespondents tried to disclose the patient's condition to the patient and/or family members. Both groups were involved in EOL care discussions, with a rather low satisfaction level (57.82/100). The best timing to initiate discussionwas consideredwhen metastasis or disease recurrence occurred orwhen withdrawal of chemotherapy was anticipated. Furthermore, the study respondents suggested that patients and their family members should be included in the EOL discussion. Medical, legal, and ethical knowledge and communication difficulties along with practical issues were revealed as barriers and facilitators for EOL discussion. This study explored various perspectives of oncologists and resident physicians for EOL discussion. Since the Life-Sustaining-Treatment Decision-Making Act will be implemented shortly in Korea, now is the time for oncologists and residents to prepare themselves by acquiring legal knowledge and communication skills. To achieve this, education, training, and clinical tools for healthcare professionals are required.